Flight dynamics of ski jumping: Wind tunnel testing and numerical modeling to optimize flight position - Barnes, J.; Tuplin, S.; Walker, A. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Ski jumping is a highly competitive sport, where the distance jumped is greatly dependent on the aerodynamic effects of the athlete`s posture. In the current paper a wind tunnel experiment was conducted to generate a parametric database of the effects of posture on aerodynamics and to compute the aerodynamic force coefficients. The parameters considered were varied over ranges representative of modern ski jumping and included the ski incidence angle, the ski V-angle, the leg-to-ski angle, and the hip angle. Measured force data were then used to simulate ski jumping flightpaths via a numerical model, allowing for the effects of posture on jump distance to be investigated. The model was able to simulate single and multi-posture flights to suggest both static and dynamic optimums. It was found that the ski jumping system generated lift in previously unreported, non-linear methods, enabling the flow to stay attached at much larger incidences than traditional wings. When optimizing posture for distance, it was found that neither lift nor efficiency (lift-to-drag ratio) should be maximized, due to the reliance on both qualities for a successful jump. However, when considering multi-posture flight, it was found that the lift-to-drag ratio should be maximized immediately after take-off, to maintain horizontal velocity. Lift should be maximized as the athlete approaches landing, due to the highly curved flightpath reducing the negative impact of drag. Realistic recommendations have been made on the postures that athletes should utilize to improve their performance. This includes a single position optimum, a "safe" optimum which allows some variation in an athlete`s ability to hold posture, and a further optimum should the athlete be skillful enough to dynamically alter posture as the jump progresses.